(untitled) (Environment & Health, 2020)
Objective: We correlated the state of refractive-accommodation system and indicators of contrast sensitivity in the students of different age groups. To solve this issue, we used the scheme of age-related periodization of a person, taking into account anatomical, physiological and social factors. Results. In each of the participants, visual acuity was detected with the help of the Golovin-Sivtsev tables, the contrast sensitivity (MS) - with the help of contrasting optotypes. An increase of the incidence of clinically significant cases of myopia with age in both girls and boys was observed in the study. Its detection rate (33.74%; n = 251) in the students, participated in our study, is almost twice as high as the detection rate of hypermetropia (17.20%; n = 128). The general tendencies of the deterioration of contrast sensitivity generally complied with the changes in the condition of the refractory apparatus in the groups of female and male students and were identical. It was revealed that in the group of persons with MS index within the range of 0-2, there were 73.04% of the total number of females and 72.00% of the total number of males with refraction disorders belonging to different age groups. Conclusions. The similarity of the tendencies in the increase of the frequency of clinically significant cases of contrast sensitivity disorders and refractive-accommodative system suggests that studies with the use of the contrasting optotype table can be used as an early method of preclinical diagnosis of refractive disorders in school-age children.